Stavovi učenika i učitelja o primjeni nastavnih medija u nastavi glazbene kulture / Students' and Teachers' Attitudes towards Application of Teaching Media in Music Lessons - Dobrota, Snježana; Novosel, Darko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
This paper has explored the attitudes of the elementary school students attending the fifth, sixth, seventh and eighth grade and the Music Culture teachers’ attitudes on the use of teaching media in music lessons. As a part of the research, The use of teaching media questionnaire for students (N=429) and The use of teaching media questionnaire for teachers (N=215) were distributed. Three variables were used for the purpose of exploring the students' attitude towards the use of teaching media in music lessons: age, gender and self-assessment of musical talent. The results confirmed that girls, compared to boys, had higher self-assessments of musical talent and participated more frequently in music activities other than compulsory music lessons. Furthermore, girls, compared to boys, more often used computers for music teaching purposes and showed greater interest in learning about music computer programs. Students generally rarely used the Music Culture textbooks, but considered introducing computers into music lessons necessary. Of all the teaching media, teachers mostly used the instrument and the textbook. Most teachers considered instruction in music computer program necessary, though teachers with shorter work experience, compared to older ones, had higher self-assessments of computer literacy. Teachers knew at least one music computer program, used the internet while preparing classes, and almost all thought that using computers improves the quality of music teaching.